Manufacturing method of 3D thermal shrinkage super-surface biochemical sensor

Through the combination of femtosecond laser process and heat shrink material PS, the problem of complex and low efficiency of traditional 3D metasurface biochemical sensor manufacturing process is solved, and the manufacturing of metasurface sensors with high sensitivity and low detection limits is achieved. The process is simple, the equipment requirements are low, and the operation is low.

CN119753676APending Publication Date: 2025-04-04BEIJING INFORMATION SCI & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657012.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The manufacturing process of traditional 3D metasurface biochemical sensors is complex, has high cost, low efficiency, and is difficult to achieve high sensitivity and low detection limits.

Method used

The femtosecond laser process is used to combine the heat-shrinking material PS to achieve efficient processing of 3D heat-shrinking metasurface biochemical sensors through the deposition of metal transition layer and metal reflective layer and laser winding irradiation.

Benefits of technology

This method can significantly improve the sensitivity of the metasurface material, reduce the size of the local structural features of the sensor, improve the aspect ratio, reduce equipment requirements and operation difficulty, shorten the preparation time, and avoid the generation of by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753676A_ABST
    Figure CN119753676A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing method of a 3D thermal shrinkage super-surface biochemical sensor, and belongs to the technical field of metamaterials. The method comprises the following steps of: 1, depositing a metal transition layer on the surface of a pyrocondensation material; 2, depositing a metal reflecting layer on the metal transition layer to obtain AS; and step 3, performing winding type irradiation on the AS obtained in the step 2 by adopting pulse laser, and controlling the number of laser irradiation turns to achieve the purpose of height, thereby realizing the processing of the 3D thermal shrinkage metasurface biochemical sensor. The 3D thermal shrinkage super-surface biochemical sensor is processed through a femtosecond laser technology, the local part of the sensor is rapidly shrunk to restore to the original shape through laser-induced thermal shrinkage by utilizing the memorability of a polymer, the feature size of the local structure of the sensor can be reduced on the premise of not changing the morphology and structural features of the sensor, the aspect ratio is increased, and the performance of the sensor is improved. And the sensitivity of the metasurface material is obviously improved. The method also has the advantages of low equipment requirement, low operation difficulty, short preparation time, no generation of byproducts in the processing process and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a 3D heat-shrinkable super-surface biochemical sensor, and in particular to a method for manufacturing a super-surface biochemical sensor based on a 3D heat-shrinkable micro-column array, and belongs to the technical field of metamaterials. Background Art

[0002] Metasurfaces are a type of artificially designed two-dimensional metamaterials, which are composed of subwavelength-scale nanostructure arrays and can control the phase, amplitude, polarization and other properties of electromagnetic waves on a subwavelength scale. Compared with traditional optical components, metasurfaces significantly reduce their volume with their ultra-thin characteristics and highly controllable surface response, and achieve more flexible optical control in infrared, visible light and terahertz frequency bands. In terms of design, metasurfaces are usually arranged by periodic or quasi-periodic structural units. By adjusting the geometric parameters and material properties of each super unit, the electromagnetic properties of the output light can be precisely controlled. Based on this characteristic, metasurfaces show broad application prospects in the fields of wavefront control, polarization conversion, color imaging and sensing. Especially in the field of sensing, by regulating the design of the structural unit to enhance the interaction with the substance to be tested, high-sensitivity detection can be achieved, which is of great significance in biomedicine, environmental monitoring and material analysis.

[0003] One promising area of ​​metasurface applications is biosensing. A biosensor is a device that detects biomolecules quantitatively or qualitatively by converting biological signals into measurable outputs. Currently, there is a wide demand for highly sensitive biosensors in areas such as cell detection, medical diagnostics, and food safety. Recently, advances have been made in optical-based biosensors, and researchers have developed metasurface-based sensors that have advantages such as high selectivity, non-invasive detection, high sensitivity, and fast response. These sensors have been studied in the microwave, optical, and terahertz frequency ranges. The working principle of metasurface sensors is to convert the refractive index changes of analytes around the metasurface into changes in the field distribution of the resonance points, which ultimately changes the response of the device. Metasurface sensors have inherent resonance peaks and are highly sensitive to refractive index changes caused by trace substances in the environment. This enhanced sensitivity allows them to outperform traditional biosensors with higher sensitivity and lower detection limits. Currently, most research efforts focus on two-dimensional (2D) metasurfaces. Compared with 2D metasurfaces, three-dimensional (3D) metasurfaces offer more hot spots and larger surface areas, resulting in higher sensitivity and lower detection limits. This progress has also driven the need for more efficient manufacturing methods. Traditionally, photolithography has been the standard technology for producing 3D metasurfaces. However, photolithography also faces many challenges: high cost and low efficiency. Photolithography involves multiple steps to manufacture three-dimensional metasurfaces, each of which may introduce potential errors. This leads to increased manufacturing errors and economic waste. To address these challenges, a promising approach is laser-induced thermal shrinkage of polymers. This technology uses the thermal shrinkage properties of certain polymers (such as polystyrene PS) to create three-dimensional structures. Unlike photolithography, this method can produce complex three-dimensional geometries by precisely applying a focused laser beam. Local laser heating induces polymer shrinkage, thereby achieving complex patterning and the formation of complex metasurface structures. This process is not only faster and more economical, but also compatible with a variety of polymer materials, expanding its potential applications in various metasurface fields. In addition, laser-induced thermal processing has obvious advantages in producing flexible and durable metasurfaces. By fine-tuning laser parameters (such as power, repetition rate, and scanning speed), metasurfaces can be designed to operate over a wide frequency range, making them particularly suitable for applications requiring broadband optical performance. For example, laser-induced metasurfaces can be optimized for use in electromagnetic shielding, terahertz communications, advanced sensing systems, and even next-generation security and communication technologies.

[0004] In summary, in order to solve the problem of difficulty in manufacturing 3D metasurface biochemical sensors, the present invention proposes a 3D metasurface sensor design combined with heat shrinkable material PS for realizing biochemical sensing. Summary of the invention

[0005] In order to solve the problem of the complexity of the traditional processing of super surface, the purpose of the present invention is to provide a 3D heat shrinkable super surface biochemical sensor manufacturing method, which uses a femtosecond laser process to process the 3D heat shrinkable super surface biochemical sensor, and can reduce the size of the characteristics of the local structure of the sensor without changing its morphology and structural characteristics, improve the aspect ratio, and significantly improve the sensitivity of the super surface material. The present invention also has the advantages of low equipment requirements, low operating difficulty, short preparation time, and no by-products due to the processing process.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention discloses a method for manufacturing a 3D heat shrinkable super-surface biochemical sensor, comprising the following steps:

[0008] Step 1: depositing a metal transition layer on the surface of the heat shrinkable material;

[0009] Step 2: depositing a metal reflective layer on the metal transition layer to obtain a metal-polymer substrate AS;

[0010] Step 3: Use pulsed laser to irradiate the metal-polymer substrate AS obtained in step 2 in a circular manner, control the number of laser irradiation circles, achieve the height purpose, and realize 3D sensor processing.

[0011] In step three, a laser with a pulse repetition rate of 100 kHz is used to irradiate the metal-polymer substrate AS obtained in step two in a circular manner.

[0012] According to the observation that PS is irradiated in a circular manner by multiple femtosecond lasers, the height of the induced cylindrical growth is positively correlated with the number of irradiation circles. The following formula is obtained by linear fitting:

[0013] h=71.35*X

[0014] Where h is the height of the cylinder growth and X is the number of femtosecond laser irradiation cycles.

[0015] Heat shrinkable super surface materials include: polystyrene PS, polyethylene PE, polyethylene terephthalate PET, polyolefin PO, and polyvinyl chloride PVC.

[0016] The metal transition layer is titanium.

[0017] The metal reflective layer is gold.

[0018] The femtosecond laser process parameters were adjusted to set the pulse repetition rate to 100kHz, the laser power to 100mW, the scanning speed to 5mm / s, and the processing line spacing to 0.02mm. The femtosecond laser was irradiated on the heat shrinkable material in a concentric ring shape to induce the structure to grow from the outside to the inside.

[0019] Beneficial effects:

[0020] 1. The present invention discloses a method for manufacturing a 3D heat-shrinkable supersurface biochemical sensor. The 3D heat-shrinkable supersurface biochemical sensor is processed by a femtosecond laser process, and a 3D supersurface structure can be obtained efficiently. At the same time, the aspect ratio required for different needs can be quantitatively adjusted according to the data fitting formula.

[0021] 2. The present invention discloses a method for manufacturing a 3D heat-shrinkable metasurface biochemical sensor, which adopts a method for preparing a metasurface structure, utilizes the memory of the polymer, and uses laser-induced heat shrinkage to make it shrink locally and quickly restore to its original state. On this basis, without changing its morphology and structural characteristics, the characteristic size of the local structure of the sensor is reduced and the aspect ratio is improved. At the same time, the sensitivity of the metasurface material is significantly improved through the gold plating process.

[0022] 3. The present invention discloses a method for manufacturing a 3D heat-shrinkable super-surface biochemical sensor. The laser processing process can be completed in just 1 hour, while the common photolithography method takes several days. Compared with conventional preparation methods, the process is simple, the equipment requirements are low, the operation difficulty is low, the preparation time is short, and no by-products are generated during the processing.

[0023] 4. The present invention discloses a method for manufacturing a 3D heat-shrinkable metasurface biochemical sensor. Increasing the pulse repetition rate to 100 kHz will lead to a reduction in the amount of material removed at the focus, thereby increasing the height of the heat-shrinkable micro-column. By adjusting laser parameters such as pulse interval and output power, the thermal effect generated in the process can be fine-tuned, thereby controlling the shrinkage of the material and ensuring that the manufactured 3D heat-shrinkable metasurface biochemical sensor structure meets the required geometric specifications. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a flow chart of a method for manufacturing a 3D heat-shrinkable metasurface biochemical sensor according to an embodiment of the present application.

[0025] Figure 2 This is the super surface graphic template of Example 1 of the present application.

[0026] Figure 3 This is a microscope image of the ultra-surface after laser processing in Example 1 of the present application.

[0027] Figure 4 This is an attempt to couple the lactose fingerprint spectrum to the sensing method of Example 1 of the present application.

[0028] Figure 5 This is a scanning electron microscope image of the supersurface after laser processing in Example 2 of the present application.

[0029] Figure 6 This is an attempt to biosensor the new coronavirus S protein in Example 2 of this application.

[0030] Figure 7 This is the super surface graphic template of comparative example 1 of the present application.

[0031] Figure 8 This is a microscope image of the ultra-surface after laser processing of Comparative Example 1 of the present application.

[0032] Fig. 9 This is a lactose fingerprint spectrum coupled sensing attempt of Comparative Example 1 of the present application.

[0033] Among them, 1-period (T), 2-cylinder radius (R), 3-outer ring width (S). DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0035] Laser-induced heat shrinkage of polymers uses the heat shrinkage properties of certain polymers (such as polystyrene PS) to create three-dimensional structures. This method can produce complex three-dimensional geometries by precisely applying a focused laser beam. The thermal effect during laser processing is used to induce polymer shrinkage, thereby achieving complex patterning and the formation of complex metasurface structures. This process is not only faster and more economical, but also compatible with a variety of polymer materials, expanding its potential applications in various metasurface fields. In addition, laser-induced heat treatment has obvious advantages in producing flexible and durable metasurfaces.

[0036] Polymer shrinkage is a method of generating structures by rearranging preformed structures. By heat-induced shrinkage of local polymers, planar structures can be given a three-dimensional shape, achieving a 3D form.

[0037] The present embodiment discloses a method for manufacturing a 3D heat-shrinkable metasurface biochemical sensor. By designing a template, a 3D metasurface structure is obtained simply and efficiently after laser-induced heat shrinkage. Figure 1 shown.

[0038] In this embodiment, the metasurface is first simulated by CST software to obtain an efficient biochemical sensor template with good characteristic peaks at a certain frequency.

[0039] Metallization of the substrate (PS) can improve the reflectivity of the metasurface and achieve better detection results.

[0040] Finally, the metasurface was processed by femtosecond laser to obtain the same structure as the simulation, and terahertz sensing tests were carried out.

[0041] Example 1

[0042] This embodiment discloses a method for manufacturing a 3D heat shrinkable metasurface biochemical sensor. After designing a template pattern on a template material, a simulation test is performed. For the structural configuration of the biochemical sensor, the meta-atoms of the metasurface are composed of simple structures (such as cylinders). It can be calculated by formula that when the height is selected as 220, 3 circles of induction by laser process are required, the structural period is selected as T=600, the radius R=80, the outer ring width S=80, and the structural unit is micrometer.

[0043] Template design: Use CST software to design template patterns (such as Figure 2 As shown in the figure, after simulation experiments, it has a characteristic peak at around 450 GHz.

[0044] Gold plating: A metal transition layer of titanium (10 nm) and a metal reflective layer of gold (200 nm) were deposited on the polymer (PS) using an electron beam deposition method to obtain a metal-polymer substrate AS.

[0045] Laser processing: The parameters were set to a pulse repetition rate of 100kHz, a laser power of 100mW, a scanning speed of 5mm / s, and a processing line spacing of 0.02mm. The femtosecond laser was irradiated in a concentric ring pattern on the heat-shrinkable material to induce the AS structure to grow from the outside to the inside, and the microcolumn height could reach 220μm. Figure 3 As shown, it is consistent with the expected result.

[0046] Test: Use a 1μM lactose solution to perform fingerprint spectrum coupling sensing test, such as Figure 4 shown.

[0047] All spectral data were obtained on the reflection test module of THz-FDS (Toptica terascan 1550, Munich, Germany). It mainly consists of two distributed feedback lasers, two fiber-coupled optical mixers, intelligent electronic devices controlled by dual lasers, and a four-mirror transmission test optical path. By testing the incident light and reflected light, the reflection spectrum of 100GHz-1440GHz was measured, and then compared with the reflection spectrum of air to obtain its reflectivity image. The test was carried out in a microchannel and the envelope of the obtained data was observed.

[0048] Example 2

[0049] This embodiment discloses a method for manufacturing a 3D heat shrinkable super-surface biochemical sensor. Template design: Use CST software to design the template pattern (same as Figure 2 As shown in the figure, after simulation experiments, it has a characteristic peak at around 450GHz. It can be calculated by formula that when the height is selected as 220, 3 circles of induction by laser process are required, the structural period is selected as T=600, the radius R=80, the outer ring width S=80, and the structural unit is micrometer.

[0050] Gold plating: A metal transition layer of titanium (10 nm) and a metal reflective layer of gold (200 nm) were deposited on the polymer (PS) using an electron beam deposition method to obtain a metal-polymer substrate AS.

[0051] Laser processing: The parameters were set to a pulse repetition rate of 100kHz, a laser power of 100mW, a scanning speed of 5mm / s, and a processing line spacing of 0.02mm. The femtosecond laser was irradiated in a concentric ring pattern on the heat-shrinkable material to induce the AS structure to grow from the outside to the inside, and the microcolumn height could reach 220μm. The structure was further observed, such as Figure 5 As shown, it is consistent with the expected result.

[0052] Test: First, modify the metasurface. The modification process is as follows:

[0053] Dithiodiglycolic acid was injected to cover the metasurface for about 24 hours, immersing the metasurface. When dithiodiglycolic acid is coated on a surface (such as a gold surface), its thiol group chemically reacts with gold atoms to form a strong gold-sulfur (Au-S) covalent bond. This bonding mode allows DTTA to be stably adsorbed on the gold surface to form a monolayer. In this structure, the carboxyl groups (–COOH) of DTTA are exposed to the outside, facing the solution or the external environment. These carboxyl groups can participate in the formation of hydrogen bonds or ionic bonds and have good reactivity and polarity, enabling interaction with other molecules in the environment. DTTA-modified gold surfaces have good biocompatibility and chemical activity and are often used in the field of biosensors and surface functionalization. An equal volume of N-hydroxysuccinimide (NHS) and 1-ethyl-3-carbodiimide (EDC) mixture was introduced and kept for 15 minutes to form a thin protein coupling layer. The surface was washed with phosphate-buffered saline (PBS) to remove any unbound EDC and NHS. Then, the new coronavirus S protein antibody was injected onto the metasurface and kept for 15 minutes to allow it to adsorb to the metasurface surface. The excess new coronavirus S protein antibody was rinsed off with PBS. Finally, a 1 μg / mL new coronavirus S protein solution was used for biosensor testing, such as Figure 6 shown.

[0054] Comparative Example 1

[0055] Template design: Use CST software to design template patterns (such as Figure 7 As shown in the figure, after simulation experiments, it has a characteristic peak at around 400 GHz.

[0056] Gold plating: A metal transition layer of titanium (10 nm) and a metal reflective layer of gold (200 nm) were deposited on the polymer (PS) using an electron beam deposition method to obtain a metal-polymer substrate AS.

[0057] Laser processing: Set the parameters to 100kHz pulse repetition rate, 300mW laser power, 5mm / s scanning speed, and 0.02mm processing line spacing. Irradiate AS with concentric rings with femtosecond laser, and only ablate it to make it a planar structure, such as Figure 8 shown.

[0058] Test: Use a 1μM lactose solution to perform fingerprint spectrum coupling sensing test, such as Fig. 9 shown.

[0059] It can be found that 3D metasurface biochemical sensors are superior to 2D planar metasurface biochemical sensors, which proves the superiority and feasibility of this method.

[0060] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing a 3D heat shrinkable super-surface biochemical sensor, characterized in that: The steps include: Step 1: depositing a metal transition layer on the surface of the heat shrinkable material; Step 2: depositing a metal reflective layer on the metal transition layer to obtain a metal-polymer substrate AS; Step 3: Use pulsed laser to irradiate the metal-polymer substrate AS obtained in step 2 in a circular manner, control the number of laser irradiation circles, achieve the height purpose, and realize 3D sensor processing.

2. The method for manufacturing a 3D heat shrinkable super-surface biochemical sensor according to claim 1, characterized in that: In step three, a laser with a pulse repetition rate of 100 kHz is used to irradiate the metal-polymer substrate AS obtained in step two in a circular manner.

3. A method for manufacturing a 3D heat shrinkable super-surface biochemical sensor according to claim 1 or 2, characterized in that: According to the observation that PS is irradiated in a circular manner by multiple femtosecond lasers, the height of the induced cylindrical growth is positively correlated with the number of irradiation circles. The following formula is obtained by linear fitting: h=71.35*X Where h is the height of the cylinder growth and X is the number of femtosecond laser irradiation cycles.

4. A method for manufacturing a 3D heat shrinkable super-surface biochemical sensor according to claim 1 or 2, characterized in that: The heat shrinkable super surface material includes: polystyrene PS, polyethylene PE, polyethylene terephthalate PET, polyolefin PO, and polyvinyl chloride PVC.

5. A method for manufacturing a 3D heat shrinkable super-surface biochemical sensor according to claim 1 or 2, characterized in that: The metal transition layer is titanium; the metal reflective layer is gold.

6. A method for manufacturing a 3D heat shrinkable super-surface biochemical sensor according to claim 1 or 2, characterized in that: The femtosecond laser process parameters were adjusted to set the parameters to a pulse repetition rate of 100 kHz, a laser power of 100 mW, a scanning speed of 5 mm / s, and a processing line spacing of 0.02 mm; the femtosecond laser was irradiated on the heat shrinkable material in a concentric ring pattern to induce the structure to grow from the outside to the inside.